MENSURAÇÃO DO DESPERDÍCIO DE MATERIAIS GERADOS NA EXECUÇÃO DE ESTACA RAIZ, ATRAVÉS DOS INDICADORES DE DESEMPENHO - Sousa, Amanda Aryda Silva Rodrigues de; Soares, George Nunes (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The civil construction companies have sought, more and more, to boost their productivity and reduce the cust of production, in order to achieve greater competitiveness, due to the current market. The civil construction industry is known for the high waste. the probability that the processes of materials and labor time, marking competitiveness a challege, justified mainly by the difficulty of managing processes, among them, the cost estimate.The objective of the analysis is the use of natural resources of performance indicators, being evaluated in a work of the municipality of Caxias, Maranhão. The research is a case study, taking a quantitative and descriptive approach. The first step of the research was seen from the executive exercise. In it were observates recursions of materials was not the service of foundation, more specifically in the execution of the stakes, for this was drawn up a plan of action. As an initial result, 0% of the 20 mm diameter bars were used, with the aid of the action plan using NBR 6118/14. Finally, the price deviation indicator has a quantitative value of 33,3% of the cost of a foundation service, having a positive impact on the company's economy.